2019
DOI: 10.51985/jbumdc2019017
|View full text |Cite
|
Sign up to set email alerts
|

Comparision Of BRAF V600E, COX–2 and p53 As Biomarkers For The Early Detection Of Colorectal Cancer

Abstract: Colorectal cancer (CRC) is one of the most common types of gastrointestinal cancer. Almost two million new cases of CRC are diagnosed every year, making CRC the third most common cancer and the fourth most common cancer-associated cause of mortality in the world. The onset and development of CRC is induced by a combination of genetic and environmental factors including social, cultural and lifestyle factors. Age is considered as main risk factor for the colorectal cancer, there is remarkable increase past the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…COX2 is involved in cell cycle control, and increased expression of COX-2 in CRC patients compared to normal controls indicates its possible role in the progression of CRC ( 40 ). COX2 influences cancer progression by increasing prostaglandin production, preventing tumor cell apoptosis, cell proliferation, and tumor angiogenesis ( 41 ). It was reported that aspirin plays a key role in preventing colon cancer by inhibiting COX ( 37 ).…”
Section: Resultsmentioning
confidence: 99%
“…COX2 is involved in cell cycle control, and increased expression of COX-2 in CRC patients compared to normal controls indicates its possible role in the progression of CRC ( 40 ). COX2 influences cancer progression by increasing prostaglandin production, preventing tumor cell apoptosis, cell proliferation, and tumor angiogenesis ( 41 ). It was reported that aspirin plays a key role in preventing colon cancer by inhibiting COX ( 37 ).…”
Section: Resultsmentioning
confidence: 99%
“…Polymorphisms in COX1 and COX2 have been associated with the development of colorectal cancer, specifically COX2, which controls the cell cycle [17] and its expression increases in response to cytokines and growth factors. COX2 participates in cancer development by increasing cell proliferation, tumor angiogenesis [18], and the production of prostaglandins that seem to increase resistance to apoptosis in epithelial cells. In contrast, in stromal cells, it favors neovascularization present in the development of CRC.…”
Section: Polyphenolsmentioning
confidence: 99%